The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/2015gb005088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trace metal‐limited growth on the postmortem dissolution of the marine diatom Pseudo‐nitzschia delicatissima

Abstract: We investigated the effects of iron (Fe) and copper (Cu) limitations on biogenic silica (bSiO2) dissolution kinetics of the marine diatom Pseudo‐nitzschia delicatissima during a 3 week batch dissolution experiment. The dissolution of this species was faster during the first week than thereafter. Modeling results from four dissolution models and scanning electron microcopy images suggested the successive dissolution of two phases of bSiO2, with two different dissolution constants. Micronutrient limitation durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
(115 reference statements)
2
15
0
Order By: Relevance
“…Iron (Fe) availability affects the growth rate, Si uptake, cell morphology and BSi content in diatoms (Leynaert et al, 2004;Hoffmann et al, 2008;Marchetti and Cassar, 2009;Boutorh et al, 2016;Meyerink et al, 2017). These microscale effects can have far reaching consequences on the physico-chemical environment, particularly in the Southern Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Iron (Fe) availability affects the growth rate, Si uptake, cell morphology and BSi content in diatoms (Leynaert et al, 2004;Hoffmann et al, 2008;Marchetti and Cassar, 2009;Boutorh et al, 2016;Meyerink et al, 2017). These microscale effects can have far reaching consequences on the physico-chemical environment, particularly in the Southern Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Model 2 is a second-order equation (2) that considers two pools of organic matter with different reactivities. It is similar to the equation that was used by Westrich and Berner (1984) for carbon degradation, and more recently it has also been employed for bSiO 2 dissolution (Moriceau et al, 2009;Boutorh et al, 2016):…”
Section: Statistical Analysis and Estimation Of Kinetic Parametersmentioning
confidence: 99%
“…It is generally admitted that a decrease in the growth rate due to nutrient stress other than Si-limitation leads to an increase of the cellular bSiO 2 content (Martin-Jézéquel et al 2000, Claquin et al 2002. However, low Si quotas have sometimes been measured for nutrientstressed diatoms in in situ or laboratory studies, which may partially be explained by the simultaneous decrease of the T. weissflogii cellular volume (Bucciarelli et al 2010;Lasbleiz et al 2014;Suroy et al, 2015;Boutorh et al, 2016). These results are contrary to what has been measured for T. pseudonana (Claquin et al, 2002) but agree well with what has been observed for T. weissflogii (De La Rocha et al, 2010), emphasizing the idea that diatoms of the same genus may have a different physiological response to environmental stress.…”
Section: Impact Of P-stress On the Initial Biochemical Composition Ofmentioning
confidence: 99%
“…All batches were incubated in the dark, at 16 • C, during 30 days on a shaking table for continuous agitation, allowing for a better homogenization of the particles in the batch. Batch cultures were kept ajar during the 30 days, in order to preserve gases exchanges, which have been proven to limit CO 2 surplus and pH changes (Suroy et al, 2014(Suroy et al, , 2015Boutorh et al, 2016). The dSi concentrations were measured on a daily basis for 4 days, and every second day until the end of the experiment.…”
Section: Dissolution Experimentsmentioning
confidence: 99%
“…Diatom frustules are surrounded by an organic coating that needs to be removed by prokaryotes before dissolution of the frustule can begin (Bidle and Azam, 2001). In addition, biogenic silica dissolution depends on nutritive growth conditions of the diatoms (Boutorh et al, 2016). The process of silicification is known to be influenced by stressful conditions, such as nutrient limitation (Boyle, 1998;Takeda, 1998;Lasbleiz et al, 2014) and/or the presence of grazers (Pondaven et al, 2007).…”
Section: Introductionmentioning
confidence: 99%